생체활성 유기물로 표면이 개질된 임플란트 개발 추이 분석 연구 - 황성택; 한인호; 허중보; 강정경; 류재준; Hwang, Sung-Taek; Han, In-Ho; Huh, Jung-Bo; Kang, Jeong-Kyung; Ryu, Jae-Jun (Taehan Chikwa Poch'ol Hakhoe chi, 2011)
Purpose: This study aims to evaluate and prospect for current research trend and developmental perspectives via analyzing recent biomaterial coated-implants study. Materials and methods: To investigate each subject respectively, several biomaterials that are using for implant surface coating were set as 'keywords'. By these keywords, major research groups in each subject were chosen, and research trend of them was analyzed. Trend of In vivo studies that examined selected biomaterials were analyzed to evaluate commercial potential. Results: The collagen research accounted for 40% of total implant study, which was the highest, and fibronectin, BMPs (bone morphogenetic proteins) and RGD (Arg-Gly-Asp) peptides followed, which were ranked in descending order. Furthermore, figures of all four research subjects were also increased with time, especially a sharp increase in RGD research. According to the results of major research group, collagen that was combined with other organic and inorganic biomaterials was mostly examined, rather than using collagen only. Major research groups investigating BMPs mostly focused on rhBMP-2. In animal studies, collagen was used as resorbable membrane in guided bone regeneration (GBR) or drug carrier, while BMPs were used with bone graft materials or coating material for titanium implant surface. Conclusion: There is not consistency of results even in identical subjects research field. Many studies are ongoing to optimize combination between mechanical surface treatment and biomaterials such as extracellular matrix component and growth factors. 연구 목적: 기존의 기계절삭 가공된 티타늄 표면에 생체활성 유기물질이 코팅된 생체 활성 임플란트에 관한연구가 최근에 많이 이루어지고 있다. 이러한 생체 활성 임플란트는 임플란트 자체에 골치유 및 골형성 효과를 부여할 수 있다. 본 연구의 목적은 생체 활성 임플란트 표면에 대한 연구 동향을 분석함으로써, 표면처리 기술 개발의 현황과 향후 발전 전망에 대해서 알아보고자 하였다. 연구 재료 및 방법: 본 문헌 분석 연구는 'Web of Science (http://isiknowledge.com, Thomson Scientific)'를 통해 SCI (science citation index) 등재 논문들을 기반으로 분석하였다. 주제별로 연구비중을 비교하기 위해서, 임플란트 표면 코팅에 사용되는 생체활성 유기물들로 키워드를 선정하고 각 키워드로 대표되는 리서치 그룹을 선정하여 각 그룹들의 연구 동향을 분석하였다. 또한 키워드별로 동물실험 동향을 분석하여 상용화 가능성에 대해서도 고찰하였다. 결과: 연구의 비중은 콜라겐, 피브로넥틴, 골형성단백질, RGD (Arg-Gly-Asp) 순으로 나타났으며, 콜라겐을 이용한 연구가 40%로 가장 많은 연구가 이루어지고 있었다. 네가지 주제 모두 시간의 경과에 따라 연구횟수가 증가하는 양상을 보였으며, 특히 RGD에 관한 연구횟수가 가장 급격하게 증가하였다. 콜라겐 대표 리서치 그룹의 연구 동향을 분석하였을 때, 콜라겐은 단독 사용보다는 다른 생체활성 유기물 및 무기물과의 병용 처치에 관해 주로 연구가 되고 있었으며, 특히 세포외기질인 콘드로이틴 설패이트와의 병용 처치에 관한 연구가 가장 많이 이루어지고 있는 것으로 나타났다. 골형성단백질의 대표 리서치 그룹들에서는 rhBMP-2 (recombinant human bone morphogenetic protein-2)에 관한 연구가 주로 이루어지고 있었다. 동물실험에 관한 연구 동향 분석 결과 콜라겐은 차폐막 혹은 약물 전달 매체로서 주로 사용되고 있었고, 골형성단백질은 치조골이식술 혹은 임플란트 표면 코팅에 대한 효과가 연구되고 있었다. 결론: 연구 결과를 주제별로 분석하였을 때 주제별로 일관성 있는 결과를 얻기 어려웠으며, 보다 나은 결과를 얻기 위한 기계적 표면처리와 여러 세포외기질, 성장인자 등의 생체물질의 최상의 조합을 찾기 위한 노력이 진행중이었다. 연구가 초기단계에 머물고 있기 때문에 상용화에 이르기까지는 많은 시간과 노력이 필요할 것이다.